A Signaling Pathway to Mediate the Combined Immunomodulation of Acetylcholine and Enkephalin in Oyster Crassostrea gigas - Liu, Zhaoqun (Front Immunol, 2020)
Molluscs have evolved a primitive but complete neuroendocrine-immune (NEI) system with a vast array of neurotransmitters to conduct both humoral and cellular immunomodulation. Previous studies have illustrated the immune functions of several key neurotransmitters. However, the combined effects of multiple neurotransmitters and the signaling pathway to mediate such immunomodulation have not been well-understood. In the present study, iTRAQ and LC-ESI-MS/MS approaches were employed to investigate the combined immunomodulation functions of two crucial neurotransmitters, acetylcholine (ACh), and [Met(5)]-enkephalin (ENK), in oyster Crassostrea gigas. A total number of 5,379 proteins were identified from hemocytes of oysters after the treatments with Ach and ENK separately or simultaneously, and 1,475 of them were found to be significantly up-regulated, while 1,115 of them were significantly down-regulated. The protein expression patterns in the groups treated by ACh and ENK separately were quite similar, which were dramatically different from that in the group treated by ACh+ENK. One hundred seventy-two proteins were found to be differentially expressed in all the three neurotransmitter treatment groups. Functional validation suggested that ACh and ENK possibly modulate the immune response in oyster hemocytes by enhancing pathogen recognition, cell apoptosis, and the enzyme activities of superoxide dismutase (SOD). Moreover, GO enrichment and co-expression network analyses implied that the combined immunomodulation of ACh and ENK might be mediated by p53, EGF-R–ErbB, and Fc gamma R (FcγR) signaling pathways. These results collectively indicated that multiple neurotransmitters executed a combined and ordered immune regulation through common signaling cascades in molluscs, which was under delicate control to maintain the homeostasis.